Effects of verbal and visual support on learning by tablet-based drawing. (May 2022) - Jamet, Eric; Michinov, Estelle
Abstract: The use of drawing has emerged as a promising approach to promoting generative learning. However, findings have been mixed, especially when no support is provided for the drawing task or when this generative task is performed on a computer. The aim of the present two studies was to assess the effect of visual (Study 1) or verbal (Study 2) support on different learning outcomes among college students working with pen-based tablets. The results of the first study ( N  = 73) showed that engaging students in a tablet-based drawing task improved their learning of pictorial information, compared with a condition where the picture was provided, but visual support (predrawn background) had no beneficial effect. In the second study ( N  = 116), providing instructions about which elements to draw first (verbal support) improved the drawings' quality and the recall of pictorial information. No effect of drawing or support on comprehension was observed in either study. Results also revealed a focused processing effect, as the learning-by-drawing strategy had a negative impact on the memorization of nonpictorial information in the text. These studies indicate that suitable support can improve the effectiveness of the drawing-based learning strategy. Further research is needed to elucidate the effects of this strategy on different learning outcomes. Highlights: We studied the effect of visual or verbal support on learning by drawing on tablets. Drawing improved the memorization of pictorial information but not comprehension. Drawing had a deleterious effect on the retention of nonpictorial information. Verbal support improved drawing quality and the learning of pictorial information.